Liberal Feminism in Nancy Springer’s Movie Script Enola Holmes - Rahma, Risky Kartika; Balqis, Kesya Aprilia; Wahyuni, Sari Indah; Nasution, Cherry Adistya; Hasibuan, Debby Melviana; Purwarno, Purwarno (Prominent, 2025)
This study explores the portrayal of liberal feminism in Nancy Springer's Enola Holmes series, focusing on how the narrative challenges societal perceptions of women's intellectual and physical capabilities. Liberal feminism, rooted in the first wave of feminism, emphasizes equality through legal reforms and individual rights. The research employs a descriptive qualitative approach to analyze Enola Holmes, highlighting the character's defiance of Victorian societal norms. Enola's rejection of traditional schooling and pursuit of autonomy underscore themes of gender equality and personal freedom. Supported by her mother, Eudoria Holmes, Enola embodies resilience and self-determination, advocating for women's rights to define their identities independently. Through qualitative analysis of dialogues and actions, this study illuminates how Enola Holmes champions liberal feminist ideals of gender equality and individual empowerment. The findings reveal Enola as a transformative figure challenging patriarchal constraints, inspiring reflection on gender roles and advocating for societal change towards equality and personal fulfillment.